Evaluation of Functional Requirements on Personal Weblog Services : Case Study in Thailand - Srisuwan, Chuthathip (2005)
Weblogs, or blogs, are frequently updated web pages containing information arranged in reverse chronological order. The number of weblogs has grown to several millions in the recent past and they represent a new trend of web publishing that influences the way people and search engines perceive the World Wide Web. The objective of this report is to identify functional requirements that contribute to the level of acceptance and use of weblog services. Therefore it employs a qualitative quantitative research approach. Based on literature and interviews, the report identifies and ranks functional requirements for weblog services from a user’s perspective. 25 of these requirements are considered to be the most significant ones. They are categorized according to the content creation process on weblogs using the categories “Community”, “Content Creation”, “Content Management”, “Content Interaction”, “Content Rendering”, and “Security’“. The resulting criteria catalogue makes it possible to evaluate a sample of 18 weblog services in Thailand regarding the features they implement. The result of the analysis shows that implementation levels vary widely among the different services and functional features. As one of the key results, it becomes obvious that the most popular services implement more features than their less popular competitors. Thus, the features offered by a weblog service seem to have an impact on its acceptance.